Design of microstrip microwave phase shifters for antenna arrays - Glushechenko, E. M. (Technology and design in electronic equipment, 2017)
The analysis of the features of microstrip discrete reflective phase shifters is given. The principle of forming multi-bit phase shifters based on the transmission-type phase shifter is presented. Two specific schemes are given as the implementation of the phase shifters.